Intuition in Organizations: Leading and Managing ProductivelyIntuition in Organizations: Leading and Managing Productively, by AgorWeston H.. Newbury Park, CA: Sage Publications, 1989. 284 pp., $18.95, paper. - Nathan, Maria L. (Academy of Management Review, 1991)
The article reviews the book ?Intuition in Organizations: Leading and Managing Productively,? by Weston H. Agor.